STUDY OF UTILIZATION OF ORGANIC RANKINE CYCLE MODULE FOR BINARY CYCLE APPLICATION IN ULUBELU GEOTHERMAL POWER PLANT - PUTU DODY WIDIANA - NIM: 23115307, I
Low temperatur brine resulted from the separation of geothermal fluid in the separator in a single flash system can be used to generate additional power in a geothermal power plant (GPP) through a binary cycle system. The binary cycle is also called the organik rankine cycle (ORC) because it uses organik working fluids. The development of ORC module technology that is available commercially at various levels of heat source temperaturw and output power will facilitate the implementation of binary cycles in GPP in Indonesia which is the conversion system is dominated by single flash system. Finally, the addition of electrical power output from the binary cycle can increase the thermal conversion efficiency of the GPP. This study discusses the utilization of low temperatur brines from GPP as a heat source to generate additional power through an ORC module. The potential of silica scalling on the surface of ORC module components is avoided by applying a closed cycle using water as a working fluid and acts as an intermediate fluid to transfer the heat from brine to the organik working fluid. The results show that the presence of closed water cycle in the binary cycle decreases the thermal efficiency of the system from 10.32% to 10.2% with gross work ouput 1630.65 kWe and net work output 1355.975 kWe, also conversion efficiency increases from 9.015% to 10.46%. This study also includes a shell-tube heat exchanger design that will be applied in closed water cycles. The heat exchanger has to meet some criteria such as heat duty requirements, allowable pressure loss, and economically production costs. An iteration process is often required to design the heat exchanger that meet those criteria. Therefore, the heat exchanger design using MATLAB is done first to avoid the iteration process that takes a long time if the design process is directly done by using HTRI. The research shows the appropriate heat exchanger geometry are tube diameter of 25.4 mm, tube length of 9.754 m, shell diameter of 1.1329 m and baffle spacing of 1 m with pressure losses at shellside and tubeside respectively 23.11 kPa and 3.54 kPa, and surface area of 670 m2 with estimated production cost of 1.39 billion rupiah. Using the information of net work output and the components needed to operate the binary cycle, financial analysis can be performed to determine the eligibility criteria of the binary cycle for real implementation in the GPP. The results show that for the scenario of feed-in tariff about $0.094/kWh, the binary cycle application is feasible for the maximum module price of $1940 per kVA to obtain net present value (NPV) of 270 million rupiah over 10 years of operating time with internal rate of return (IRR) of 12.08%. And for feed-in tariff scenario in accordance with PERMEN ESDM No. 17 Tahun 2014, binary cycle application is still feasible for the module price of $3000 per kVA with a NPV of 16.4 billion rupiah, IRR of 15.42% and a 9 year payback period.